Effects of High Loss on Ignition Fly Ash as a Partial Replacement for Sand on the Properties of Mortars - Thuy, Nguyen Thi Bich; Tangtermsirikul, Somnuk; Mien, Tran Van; Kiet, Bui Anh (Engineering, Technology & Applied Science Research, 2024)
This study investigates the effects of fly ash with a high unburned carbon content as a partial sand replacement material on the properties of mortars. Fly ash was added to the mortar in four different ratios: 0, 10, 30, and 50% by volume. This study examined two series of mortar mix proportions, one having a controlled water-to-cement ratio and the other having a controlled flow. The fresh properties and compressive strength of the mortars were investigated. The experimental results showed that the compressive strength increased with increasing fly ash-to-aggregate ratio (FA/A). However, the increase in FA/A resulted in higher water requirements, lower flow, and longer setting times. The calcium hydroxide content and total porosity of the mortars were also examined to support the results of the compressive strength tests. Based on the results, the FA/A ratio had a significant impact on the fresh properties and compressive strength of the mortars. To ensure fresh properties and compressive strength of mortars, a fly ash-to-sand ratio of up to 30% is recommended.